Management of Elementary and Regular Classes for Elementary School Students from the Implementation and Planning of Idea - Jihan Syafira Rustanto; Bambang Sigit Widodo; Amrozi Khamidi (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe the management of excellent and regular classes at SD Hang Tua 10 Juanda. This research is field research conducted using qualitative methods with a case study research design. Data collection techniques include observation, interviews, and documentation. Data analysis involves data condensation, data presentation, and verification of conclusions. This study tested credibility, transferability, dependability, and confirmability to ensure data validity. The research findings reveal the implementation of the excellent class and regular class programs, covering aspects such as planning (objectives, management, curriculum, costs), implementation (administrators, educators, students, materials, scheduling, facilities, costs), evaluation, and comparing the results with existing standards. This evaluation is usually conducted during mid-term or end-of-term assessments, where reports from each excellent class or regular class teacher are submitted to the headmaster. The evaluation examines whether the objectives of the excellent class program, as measured by student learning through exams or assessments, have been achieved. If not, improvements will be made. However, if the learning process and outcomes align with the established standards, enrichment activities will be implemented to maintain or enhance student learning achievements.